The effect of teaching positive thinking skills on optimism and academic enthusiasm of school students - Elahe Naghizadeh; Yousef Namvar; Asghar Nakhostin Goldoost (مطالعات روانشناسی تربیتی)
The present study was conducted with the aim of investigating the effect of teaching positive thinking skills on optimism and academic enthusiasm of elementary school students in Ardabil city. The present research method was a semi-experimental pre-test-post-test type with a control group and a 3-month follow-up. The statistical population of the research included all the female students of the second year of elementary school (4945 people) in the city of Ardabil in the academic year 1402-1403, from which 60 people were selected as a sample by random cluster sampling, and in two groups of 30 people (30 people in the experimental group and 30 people of the control group) were randomly replaced. To collect data, academic optimism questionnaires by Schennen Moran et al. (2013) and academic enthusiasm by Wang et al. (2011) were used. To analyze the data, the analysis of variance test with repeated measurements was used in SPSS.24 software. The findings showed that teaching positive thinking skills leads to an increase in academic optimism in elementary school students (p<0.01); Also, positive thinking training was effective in improving the academic enthusiasm of primary school students and the results of this effect were stable in the period of 3 months (p<0.01). According to the results of this study, positive thinking skill training can be considered as a preventive program for students who have problems and defects in academic and emotional fields or as an intervention program to reduce harm in children and adolescents, especially by therapists and counselors. be placed